2020
DOI: 10.7150/jbji.46199
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Blue Light and Photosensitizers on Cutibacterium acnes on Shoulder Periprosthetic Joint Infection Isolates

Abstract: Abstract. Introduction: Cutibacterium acnes is gaining recognition as a leading pathogen after orthopaedic shoulder procedures. Photodynamic therapy, a combination of light and a photosensitizer, has demonstrated antimicrobial activity against C. acnes in the treatment of acne vulgaris. We sought to evaluate the effect of photodynamic therapy using blue light and photosensitizers on C. acnes isolates from shoulder prosthetic joint infections.Methods: C. acnes strains isolated from 19 patients with shoulder PJI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 38 publications
(53 reference statements)
0
9
0
Order By: Relevance
“…It is associated with the current inflammation, also with the participation of melanocytes (which increases the likelihood of postinflammatory hyperpigmentation), increased microcirculation (acne lesions are characterized by lymphocytic infiltration and an increase in the expression of inflammatory vascular markers, e.g., VCAM-1, ICAM-1), which promote angiogenesis 21,22 and involving Cutibacterium acnes, producing porphyrins. 23 The melanin absorbs a wide range of the light spectrum, and the longer the wavelength, the less light is absorbed by melanin. 24 The melanin is one of the first chromophores to encounter light in its path.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is associated with the current inflammation, also with the participation of melanocytes (which increases the likelihood of postinflammatory hyperpigmentation), increased microcirculation (acne lesions are characterized by lymphocytic infiltration and an increase in the expression of inflammatory vascular markers, e.g., VCAM-1, ICAM-1), which promote angiogenesis 21,22 and involving Cutibacterium acnes, producing porphyrins. 23 The melanin absorbs a wide range of the light spectrum, and the longer the wavelength, the less light is absorbed by melanin. 24 The melanin is one of the first chromophores to encounter light in its path.…”
Section: Discussionmentioning
confidence: 99%
“…The low reflectance in the range of 400–599 nm may be caused by the accumulation of chromophores in the skin that absorbs waves in this range, 20 which would explain the lowest skin reflectance in cases with moderate acne. It is associated with the current inflammation, also with the participation of melanocytes (which increases the likelihood of postinflammatory hyperpigmentation), increased microcirculation (acne lesions are characterized by lymphocytic infiltration and an increase in the expression of inflammatory vascular markers, e.g., VCAM‐1, ICAM‐1), which promote angiogenesis 21,22 and involving Cutibacterium acnes, producing porphyrins 23 …”
Section: Discussionmentioning
confidence: 99%
“…Ultraviolet in combination with photosensitizing antibiotics against C. acnes has also been studied as a prophylactic 40,41 . Bhargava et al 40 found that 94% of C. acnes strains (16 of 17) isolated from shoulder PJI were sensitive to blue light with demeclocycline (a tetracycline antibiotic used as a photosensitizer) in vitro. Cotter et al 41 evaluated the efficacy of BPO, blue light therapy (BLT), and BPO followed by BLT against C. acnes in shoulder arthroplasty patients.…”
Section: Prehospitalization Preoperative Skin Regimensmentioning
confidence: 99%
“…Porphyrins—products of C . acnes metabolism—are aromatic compounds, classified as photosensitizing substances, intensively absorbing light with a wavelength of 400–450 nm, and to a lesser extent in long visible bands, such as orange (590–635 nm) and red light (635 –700 nm) 20 …”
Section: The Effectiveness Of In Vitro Light Therapymentioning
confidence: 99%
“…Porphyrins-products of C. acnes metabolism-are aromatic compounds, classified as photosensitizing substances, intensively absorbing light with a wavelength of 400-450 nm, and to a lesser extent in long visible bands, such as orange (590-635 nm) and red light (635 -700 nm). 20 The wavelength determines not only the absorption behavior but also the depth of light penetration-in the visible spectral range, the latter increases with wavelength. By using different cutoff filters (515-755 nm), which only allow a specific spectrum to be penetrated, the optimal wavelength spectrum can be filtered to suit the target structure depth (vessels of different depths and sizes, hair follicles, pigment structures).…”
Section: The Effec Tivene Ss Of In Vitro LI G Ht Ther Apymentioning
confidence: 99%